Diastereoselective diazenyl formation: the key for manganese-catalysed alcohol conversion into (E)-alkenes. Issue 37 (9th September 2019) - Azofra, Luis Miguel; Poater, Albert
Abstract : The proposed reaction mechanism for the unprecedented direct transformation of primary alcohols into alkenes catalysed by Mn(i )-PNP complexes consists of two cycles. Abstract : The proposed reaction mechanism for the unprecedented direct transformation of primary alcohols into alkenes catalysed by Mn(i )-PNP complexes consists of two cycles. First, the acceptorless dehydrogenation of the alcohol into aldehyde is produced via a concerted mechanism. Secondly, in an excess of hydrazine, hydrazone is formed and reacts with the aldehyde to produce olefins. This process, taking place in base-free conditions, is characterised by the diastereoselective formation of diazenyl intermediates. Based on DFT data, the generation of the ( S N, S, S ) diastereoisomer is favoured over the rest, leading in its decomposition to the preferential formation of an ( E )-alkene and liberating N2 and H2 O as the only by-products.